U.S-Turkey Crisis and Its Impact on the Economy of the Black Sea Region - George Abuselidze; Lela Mamaladze (E3S Web of Conferences, 2019)
The process of political, economic and socio-cultural integration is underway of rapid pace in terms of globalization. Consequently, changes in one state will be reflected in other countries or region as a result of increased interdependence. The U.S. and Turkey have a historically strong relationship. They have a shared interest in economic collaboration, stability and security. The long history partnership has been tested in 2018 by a series of disagreements. Turkey and the U.S face their greatest diplomatic crisis. The lira lost almost a quarter of its value against the dollar. It should be noted Turkey's increasing more independent regional role and influence. There are also signs that the crisis has the wider impact. However, the aim of this paper is to present the correlation between the U.S-Turkey crisis and the economy of the Black Sea Region countries. The paper consists of several thematic parts and a part dedicated to conclusions and recommendations. First one is introduction, second one is theoretical and provides to analyze specific issues related to US-Turkey relations: from alliance to crisis. The third part discusses the research methodology used during the research for this study. The article includes short and long term recommendations which are possible solutions for it. – – Der Prozess der politischen, wirtschaftlichen und soziokulturellen integration schreitet im Hinblick auf die Globalisierung rasant voran. Infolgedessen werden sich die Veränderungen in einem Staat in anderen Ländern oder Regionen infolge der zunehmenden Interdependenz widerspiegeln. Die USA und die Türkei haben eine historisch starke Beziehung. Sie haben ein gemeinsames Interesse an wirtschaftlicher Zusammenarbeit, Stabilität und Sicherheit. Die langjährige Partnerschaft wurde 2018 durch eine Reihe von Meinungsverschiedenheiten getestet. Die Türkei und die USA stehen vor Ihrer größten diplomatischen Krise. Die lira verlor fast ein Viertel Ihres Wertes gegenüber dem dollar. Es sei darauf hingewiesen, dass die Türkei zunehmend Unabhängiger von regionaler Rolle und Einfluss wird. Es gibt auch Anzeichen, dass die Krise die größeren Auswirkungen hat. Ziel dieses Papiers ist es jedoch, die Korrelation zwischen der US-Türkei-Krise und der Wirtschaft der Länder des Schwarzen Meeres darzustellen. Das Papier besteht aus mehreren thematischen teilen und ein Teil gewidmet Schlussfolgerungen und Empfehlungen. Die erste ist die Einführung, die zweite ist theoretisch und bietet die Analyse spezifischer Probleme im Zusammenhang mit den Beziehungen zwischen den USA und der Türkei: von Allianz zu Krise. Der Dritte Teil behandelt die Methodik der Forschung bei der recherche für diese Studie. Der Artikel enthält kurz-und langfristige Empfehlungen, die mögliche Lösungen dafür sind.
Keywords: F01; F02; F36; F51; F63; H12; O51; O52; 330; Crisis; sanctions; trade relations; Black Sea region